PERUBAHAN STRUKTUR AGRARIA DI HULU DAS CIDANAU KABUPATEN SERANG PROVINSI BANTEN - Hidayat, Hidayat (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
The course of peasant’s history in Indonesia was colored by superlocal power domination in the form of which vary from time to time depending on the political interest and economical regime of the ruling class. The agrarian politics which oriented betting on the strong had complex impact towards rural community that caused productivity of agricultural, forestry and economic growth. But the agrarian politic capitalist that caused disparity of land of property, disparity of agrarian structure and peasant marginalization. The capitalization of agrarian resouces was due to depesanitation process systematically occurred over level system ( rule of laws and policy of regulation), level organization and caused the ruling government had failed to create the objective of institutional for prosperity at large and people’s welfare. The agrarian politics was failured to peasant empowerment economic aspects and conducive agrarian resources for sustainability development.